Cutting cosmos : masculinity and spectacular events among the Bugkalot - Mikkelsen, Henrik Hvenegaard (Ethnography, theory, experiment, 2018)
"For the first time in over 30 years, a new ethnographic study emerges on the Bugkalot tribe, more widely known as the Ilongot of the northern Philippines. Exploring the notion of masculinity among the Bugkalot, Cutting Cosmos is not only an experimental, anthropological study of the paradoxes around which Bugkalot society revolves, but also a reflection on anthropological theory and writing. Focusing on the transgressive acts through which masculinity is performed, this book explores the idea of the cosmic cut, the ritual act that enables the Bugkalot man to momentarily hold still the chaotic flows of his world"--